Optical-televiewer-based reconstruction of firn densification, layering and vertical strain: Roi Baudouin Ice Shelf, Antarctica - Hubbard, Bryn; Tison, Jean-Louis; Pattyn, Frank; Philippe, Morgane; Malone, T. (2013)
info:eu-repo/semantics/published